Apoyo Emocional de la Pareja Durante el Embrazo, Puerperio y Postparto: Percepciones de un Grupo de Mujeres del Municipio de Uribía
This research aimed to analyze the perception of women from Uribia regarding their partner's emotional support during pregnancy and postpartum. As a methodological means, the qualitative approach, descriptive type and phenomenological design was used in a sample of 10 women through focus groups and semi-structured interviews. The results indicated that emerging categories such as reciprocal support and understanding are fundamental for the birth and postpartum process, since they are relevant to facing difficulties. On the other hand, assertive communication. Empathy and active listening were emerging categories as abilities to resolve conflicts and support the couple emotionally; likewise, the lack of attention and communication causes negative emotional feelings in the woman